Evaluation of vascular healing of polymer-free sirolimuseluting stents in native coronary artery stenosis: A serial follow-up at three and six months with optical coherence tomography imaging - Pannipa Suwannasom (2018)
© Europa Digital & Publishing 2016. All rights reserved. Aims: Our aim was to assess vascular response after polymer-free sirolimus-eluting stent (SES) implantation by using an optical coherence tomography (OCT)-derived vascular healing score (HS), quantifying the deficiency of healing. Methods and results: In a prospective, multicentre, single-arm, open-label study, OCT examinations were performed at three months in 45 patients (47 lesions). Per protocol, 24 lesions which had not reached adequate vascular healing according to study criteria were scheduled for OCT examination at six months. The HS was calculated at two time points. Serial OCT imaging demonstrated that the proportion of covered stent struts increased from a median of 87.1% at three months to 98.6% at six months (p<0.001). The neointimal thickness increased from a median of 82.8 μm to 112.2 μm (p<0.001), whereas the median percentages of malapposed struts were 0.2% and 0.0% at the two respective time points. Neointimal volume obstruction increased from 6.3% to 12.8%, and the HS decreased from a median of 28.1 at three months to 2.4 at six months. Conclusions: In patients who had inadequate vascular healing three months after polymer-free SES implantation, serial OCT showed almost complete vascular healing at six months. (ClinicalTrials.gov Identifier: NCT01925027)